Dampak Variasi Iklim Terhadap Produktivitas Mangga (Mangifera indica) Di Kabupaten Indramayu, Jawa Barat - Triani, Fuji; Ariffin, Ariffin (PLANTROPICA: Journal of Agricultural Science, 2019)
Climate change has a significant impact in various sectors, especially the agricultural sector. Climate variations that have significant changes are rainfall and temperature. One of the effects of climate change is that it can reduce the productivity of mango (Mangifera indica). Mango (Mangifera indica) is a fruit of high economic value and is an important food ingredient after bananas for people in tropical climates. The purpose of this study was to determine the effect of variations in climatic elements on mango productivity in Indramayu Regency. The study was conducted in February-April 2018 in Indramayu Regency, West Java in selected sub-districts (Hargeulis, Gantar, Indramayu and Balongan) as mango production centers. This study uses an independent (independent) variable analysis with the dependent variable in this analysis which is the independent variable namely the climate elements while the dependent variable is the productivity of mango. By using a simple regression test and multiple regression. The results showed that the climatic element influencing the productivity of mangoes in Indramayu Regency was temperature. From the results of the relationship of climate change with mango productivity shows that the equation model Y = 18.54-0.28x1 + 0.52x2-0.85x3 is obtained.